An efficient reversible data hiding based on improved pixel value ordering method - Luyen, Cao Thi; Sao, Nguyen Kim; Quang Hoa, Le; Minh Thanh, Ta (Journal of Computer Science and Cybernetics, 2022)
Pixel value ordering (PVO) has been considered as an effective reversible data hiding method for high embedding capacity and good imperceptibility. In this paper, we propose a novel reversible data hiding based on four sorted pixels. This paper proposes a new reversible hiding scheme based on the arrangement of 4 pixels. Three bits will be embedded into each four pixels sub block without changing the order while the original PVO method only embeds 2 bits. In case the amount of payload is less than the embedding capacity, flatter blocks will be prioritized for embedding to improve image quality. To determine the flat of block, we use 12 neighborhood pixels of current block. Only blocks with satisfactory flatness are used for embedding. The proposed reversible data hiding not only gains high capacity but also gets good imperceptibility. Experimental results also show that the proposed reversible data hiding scheme outperforms several widely schemes using pixel value ordering method in terms of both image quality and embedding capacity.